MENGIDENTIFIKASI FAKTOR PENGHAMBAT PEMBELAJARAN MATERI KENAMPAKAN ALAM DAN BUATAN PADA SISWA SEKOLAH DASAR - Lutvia Ainun Hazizah; Randita Lestari; Salsa Nabila Marcella Kalalo; Tin Rustini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Social studies is one of the subjects by studying various disciplines so that students are able to participate in social life, society, country and the world. The study of material in social studies subjects consists of sociology, geography, sociology, and economics. Natural features material is included in the study of geography in the map chapter. In the learning process, there are always inhibiting factors, whether it is from outside or from within, this affects student learning outcomes. The research method is carried out using qualitative methods of literature study by looking for references through journals, books, and others from previous researchers. The results of this study based on research using literature studies, found several problems in the implementation of Social Sciences (IPS).